Efficacy and safety of polymyxin E sulfate in the treatment of critically ill patients with carbapenem-resistant organism infections - Lu, Xin; Zhong, Cejun; Liu, Yanbin; Ye, Hui; Qu, Junyan; Zong, Zhiyong; Lv, Xiaoju (Frontiers in Medicine, 2022)
Objective: Polymyxins are currently the last line of defense in the treatment of carbapenem-resistant organisms (CRO). As a kind of polymyxin available for clinical use in China, we aim to explore the efficacy and safety of colistin sulfate (Polymyxin E sulfate, PES) in this study. Methods: This real-world retrospective study included 119 patients diagnosed with CRO infection and treated with PES for more than 72h, from May 2020 to July 2022 at West China Hospital. The primary outcome was clinical efficacy at the end of treatment, and secondary outcomes included microbial response, in-hospital mortality and incidence of nephrotoxicity. Results: The effective clinical and microbiological responses were 53.8% and 49.1%, respectively. And the in-hospital mortality was 27.7%. Only 9.2% of patients occurred with PES-related nephrotoxicity. Multivariate analysis revealed that duration of PES was an independent predictor of effective therapy, while age-adjusted Charlson comorbidity index (aCCI) and post-treatment PCT(p-PCT) were independent risk factors for poor outcome. Conclusions: PES can be a salvage treatment for CRO-induced infections with favorable efficacy and low nephrotoxicity. The treatment duration of PES, aCCI and p-PCT were factors related to the clinical effectiveness of PES.